Helicobacter Pylori Infection Among Patients Undergoing Upper Gastrointestinal Endoscopy For Dyspepsia - Bhattarai , Subash; Dhungana, Durga; Regmi, Sudeep (Nepal Journal of Medical Sciences, 2021)
Introduction: Helicobacter pylori is associated with the pathogenicity of gastroduodenal mucosal lesions, ulcers, and gastric cancers. The present study was undertaken to study the prevalence of H. pylori infection among patients undergoing upper gastrointestinal (UGI) endoscopy for dyspepsia in the Nepalese population. Methods: A cross-sectional, hospital-based study was conducted among patients presenting with dyspepsia. Each study patient underwent upper gastrointestinal endoscopy followed by a rapid urease test or histopathology from the biopsy sample for H. pylori detection. Data analysis was done by SPSS 20. Results: The mean age of the patients was 43±11.65 years (M: F=1.4:1) with male predominance. The prevalence of H. pylori infection was 53.2% among the dyspeptic patients undergoing UGI endoscopy. The H. pylori infection was significantly associated with gastritis, duodenitis, gastric ulcer, duodenal ulcer, and gastric cancer (p <0.05). Conclusion: This study demonstrates a high prevalence of H. pylori among patients undergoing UGI endoscopy for dyspepsia.